The Values Of Moral Education In Surah Al-Hujurat 1-5 According To Tafseer Al-Munir - Heru Saiful Anwar; Ahmad Basheikh Romadhon (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
The background of this research is the fact that the Qur'an is the word of Allah that is revealed to the Prophet Muhammad SAW, as a guideline for mankind in the obligation to serve as servants of Allah SWT and instruction in organizing his life to be according to the religion and At the end of this era the decline of Muslims is caused by several factors, one of which is moral decay. Morality is a very expensive and difficult thing to look for in this day and age. lack of understanding of the moral values contained in the Qur'an will further aggravate a person's personal condition. To form a noble person, moral cultivation should be implemented as early as possible so as to facilitate its formation compared to later adulthood, because personality or good character has a major role in the development of humanity and Islamic civilization. In this case researchers want to uncover the values of the moral education contained in one of the letters of Al-Qura'an namely the surah of Al-Hujurat paragraph 1-5 based on one of the interpretations of Al-Munir